Respuesta :
Answer:
y - 6 = (3/4) (x + 4)
Explanation:
The general form of the linear line in point-slope form is:
y - y1 = m (x - x1)
where
m is the slope
(x1 , y1) are the coordinates of the given point on the line
In the give, we have:
m = 3/4
x1 = -4
y1 = 6
Substitute with the givens in the above formula to get the equation as follows:
y - y1 = m (x - x1)
y - 6 = (3/4) (x - -4)
y - 6 = (3/4) (x + 4)
Hope this helps :)
y - 6 = (3/4) (x + 4)
Explanation:
The general form of the linear line in point-slope form is:
y - y1 = m (x - x1)
where
m is the slope
(x1 , y1) are the coordinates of the given point on the line
In the give, we have:
m = 3/4
x1 = -4
y1 = 6
Substitute with the givens in the above formula to get the equation as follows:
y - y1 = m (x - x1)
y - 6 = (3/4) (x - -4)
y - 6 = (3/4) (x + 4)
Hope this helps :)